2017
DOI: 10.1007/s12576-016-0516-6
|View full text |Cite
|
Sign up to set email alerts
|

Time-course investigation of blood–brain barrier permeability and tight junction protein changes in a rat model of permanent focal ischemia

Abstract: Permanent middle cerebral artery occlusion (pMCAO) is an animal model that is widely used to simulate human ischemic stroke. However, the timing of the changes in the expression of tight junction (TJ) proteins and synaptic proteins associated with pMCAO remain incompletely understood. Therefore, to further explore the characteristics and mechanisms of blood-brain barrier (BBB) damage during cerebral ischemic stroke, we used a pMCAO rat model to define dynamic changes in BBB permeability within 120 h after isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Several authors have reported that pMCAO and GCIR cause disruption of the neurovascular barrier (Liu et al . ,b), while it remains intact after CCH (Farkas et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported that pMCAO and GCIR cause disruption of the neurovascular barrier (Liu et al . ,b), while it remains intact after CCH (Farkas et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain relief was by subcutaneous administration of Marcainâ (1.25 mg/ kg). The endpoint of each model was set in regard to the central neuronal injury (Mracsk o et al 2010;Cheng et al 2016;Svensson et al 2016;Liu et al 2017b), and no impact on enteric neurons is to be expected until after the brain injury.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, ZO-1, claudin-5, and occludin are the most important proteins in TJs. Mounting evidence indicates that the increased permeability of BBB induced by ischemia generally correlates with the alterations of ZO-1, claudin-5, and occludin (Cao et al, 2016a;Page et al, 2016;Yu et al, 2017;Liu et al, 2018). In this work, the results demonstrated that although TGs could significantly increase the expressions of ZO-1, claudin-5, and occludin proteins in MCAO-induced brain tissues, neither PSs nor OSs did.…”
Section: Discussionmentioning
confidence: 52%
“…Triphenyltetrazolium chloride staining was performed as described in our previous report . After behavioural test, the mice were killed and the brains were sectioned at the QA‐injected position and stained with 2% solution of TTC at 37°C in the dark for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%